Hepatic anisakiasis mimicking metastatic liver tumour. (2019) - Kita, Ryosuke; Hashida, Hiroki; Uryuhara, Kenji; Kaihara, Satoshi
Highlights: Anisakiasis is a parasitic disease caused by anisakid nematode larvae in raw fish. Anisakiasis may increase with growing consumption of raw fish around the world. Hepatic anisakiasis presents as small, low density tumours in the liver margin. The lesions resemble recurrent carcinoma, and can lead to unnecessary surgery. Dietary investigation is warranted when liver tumour malignancy is not certain. Abstract: Introduction: Anisakiasis is a parasitic disease caused by anisakid nematode larvae, which are found in raw or undercooked fish. It occurs more frequently in the digestive tract, but has also been reported outside the gastrointestinal tract. This report details a case of rare hepatic anisakiasis that was initially diagnosed as metastatic rectal cancer. Presentation of case: A 60-year-old male underwent radical resection for stage III rectal cancer followed by adjuvant chemotherapy for six months. Seven months after surgery, a new, 10 mm diameter area of low density was seen in segment 4/8 margin of the liver on enhanced computed tomography (CT) scan. Metastatic liver tumour from rectal cancer was suspected. Laparoscopic partial hepatectomy was performed. The diagnosis was revised to hepatic anisakiasis when pathological examination revealed anisakis simplex larvae in the necrotic tissue. Discussion: Anisakiasis outside of the gastrointestinal tract is a rare finding, but may be seen more frequently with the recent increase in the consumption of raw fish around the world. Hepatic anisakiasis may mimic tumours in the liver. Clinicians should consider dietary inquiry and further evaluation in patients with liver margin tumours less than 20 mm in size that are not positively malignant, as hepatic anisakiasis may be a possible diagnosis. Conclusion: We report a rare case of hepatic anisakiasis which initially presented as suspected metastatic cancer. Hepatic anisakiasis should be considered in the differential diagnosis of low density liver tumours less than 20 mm, where the patient's diet includes raw fish.